PERANAN MODAL SOSIAL PADA KAMPUNG PATIN DESA KOTO MASJID KABUPATEN KAMPAR - Mei Indayut Titin Ainin; Adianto Adianto (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
This study aims to determine the role of social capital and factors that drive the role of social capital in the Koto Mesjid Village. Study uses Putnam (2000) theory that social capital is divided into three forms, namely trust, network and norms that are applied in encouraging success of technology-based catfish farming. This study uses qualitative method with case study approach. Informants in this study were Head of PMD Section XIII Koto Kampar, Koto Mesjid Village government, Head of Bumdes, Innovators, and community of Koto Mesjid Village. Selection of informants using purposive sampling technique. Data collection is done by observation, interviews, documentation. Data analysis used is qualitative data analysis. The results showed that role of social capital in technology-based catfish farming practices went well. Driving factors for the role of social capital that researchers found in field were that community was still homogeneous, there was public awareness, and motivation for profits earned by community.